Analysis of conditions and criteria for shock pulse reproducibility on mechatronic test stands - A. K. Vasiliev; V. A. Dyachenko (Омский научный вестник)
Repeated impact testing is an important part of any product development. The tests are carried out on stands of repeated blows. In order to expand the range of functional parameters of mechatronic stands of multiple blows, the following are proposed: criteria for choosing the parameters of an air suspension, a method for predicting changes in the stiffness of a shaper during stand operation, and a method for assessing the effect of the reproducibility of controlled parameters on the stability of a shock pulse. In contrast to the known works, the proposed criteria and methods take into account the requirements for the reproducibility of the shock impulse.